2014
DOI: 10.1186/1476-511x-13-195
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of feeding fructose, glucose and sucrose on blood lipid levels and systemic inflammation

Abstract: BackgroundRecent studies have demonstrated a relationship between fructose consumption and risk of developing metabolic syndrome. Mechanisms by which dietary fructose mediates metabolic changes are poorly understood. This study compared the effects of fructose, glucose and sucrose consumption on post-postprandial lipemia and low grade inflammation measured as hs-CRP.MethodsThis was a randomized, single blinded, cross-over trial involving healthy subjects (n = 14). After an overnight fast, participants were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 32 publications
0
51
1
Order By: Relevance
“…The supplementation of a normal diet with 3 × 75 g of sucrose results in a repeated transient ∼50% and 700% increase in blood glucose and insulin, respectively (Jameel et al . ). The response curve to sucrose is similar to that of a standard oral glucose tolerance test and blood glucose returns to initial levels after 2 h in the morning and after 3 h at midday and in the evening (Jarrett et al .…”
Section: Discussionmentioning
confidence: 97%
“…The supplementation of a normal diet with 3 × 75 g of sucrose results in a repeated transient ∼50% and 700% increase in blood glucose and insulin, respectively (Jameel et al . ). The response curve to sucrose is similar to that of a standard oral glucose tolerance test and blood glucose returns to initial levels after 2 h in the morning and after 3 h at midday and in the evening (Jarrett et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other plasma indicators of metabolic syndrome, such as plasma glucose, lipids and hsCRP, were not significantly altered in response to acute fructose/glucose load in our study. The lipidaemic and pro‐inflammatory effects of fructose ingestion have been reported in several studies, with heterogeneous results . In a cross‐over study of 14 normal‐weight, Australian participants, a single acute dose of fructose produced a significant increase in hsCRP, total cholesterol, LDL and HDL cholesterol but no significant change in TG .…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Cholesterol, low‐density lipoprotein, and high‐density lipoprotein changes in the blood have been reviewed in detail by Jameel et al. [ 10 ] They discussed the role of fructose, glucose, and sucrose in this context and concluded that fructose has the greatest impact on blood lipids. Readers are referred to, for example, the recent review of Kearns et al.…”
Section: Effects On Healthmentioning
confidence: 99%